Engineering of a Core–Shell Nanoplatform to Overcome Multidrug Resistance via ATP Deprivation. Issue 20 (18th September 2020) - Liu, Genhua; Wang, Liucan; Liu, Junjie; Lu, Lu; Mo, Dong; Li, Ke; Yang, Xin; Zeng, Rui; Zhang, Jixi; Liu, Peng; Cai, Kaiyong
Abstract: Inhibiting the function of P‐glycoprotein (P‐gp) transporter, which causes drug efflux through adenosine triphosphate (ATP)‐dependent manner, has become an effective strategy to conquer multidrug resistance (MDR) of cancer cells. However, there remains challenges for effective co‐delivery, sequential release of P‐gp modulator and chemotherapeutic agent. In this work, a novel type of core–shell nanoparticle is reported. It can independently encapsulate a high amount (about 683 µg mg −1 ) of chemotherapeutic agent doxorubicin (DOX) in the mesoporous polydopamine (MPDA) core and glucose oxidase (GOx) in the zeolite imidazolate frameworks‐8 (ZIF‐8) shell, namely MPDA@ZIF‐8/DOX+GOx. The fast release of GOx triggered by acid‐sensitive degradation of the ZIF‐8 shell consumes glucose to starve cancer cells for ATP deprivation and effective suppress ATP‐dependent drug efflux in advance, and then effectively facilitates the accumulation of DOX in MCF‐7/ADR cancer cells. Experiments in vitro and in vivo demonstrate that the fabricated nanosystem can dramatically improve anticancer effects for MDR through sequential release property and exhibit excellent biocompatibility. Overall, this work reveals new insights in the use of GOx for MDR treatment. Abstract : The GOx and DOX are co‐loaded into core–shell MPDA/ZIF‐8 nanosystem to realize starvation‐therapy and enhanced‐chemotherapy. The first released GOx via acid‐triggered ZIF‐8 degradation starves cancer cells, leading to ATP deprivation to suppress P‐gp function. The subsequent release of DOX could efficiently be accumulated for conquering MDR of cancer cells.